MODELING METHOD IN TEACHING RUSSIAN AS A FOREIGN LANGUAGE (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article discusses the issue of using the modeling method in teaching Russian as a foreign language. It is noted that when teaching this language, the use of various models is especially effective, helping to better master the material on the topic.